Preconception exposure to environmental antibiotics among childbearing couples in Anhui and health risk assessment: A multicenter population-based representative study - Baolin Wang; Menglong Geng; Mengdie Li; Xiaorui Wang; Hong Gan; Ying Tang; Qianhui Yang; Yuwei Liu; Xinliu Yang; Sheng Wang; Kaiyong Liu; Zhaolian Wei; et al. (Ecotoxicology and Environmental Safety, 2023)
Only few studies have assessed the health effects due to preconception exposure to antibiotics among childbearing couples. This study investigated the status of preconception exposure to antibiotics among childbearing couples in Anhui, associated with health risks, and influencing factors. Overall, 1500 childbearing couples were randomly selected from the Reproductive Health of Childbearing Couples - Anhui Cohort (RHCC-AC). The urinary levels of 40 antibiotics and 2 metabolites were determined, and specific gravity (SG) adjusted concentrations of antibiotics were measured to assess health risks. Generalized linear models were used to assess the associations of urinary SG-adjusted concentration of antibiotics with demographic parameters and diet frequency. The total detection rates of all antibiotics were 98.9 % and 99.3 % in wives and husbands, respectively. The detection rates of veterinary antibiotics (VAs) and preferred as VAs (PVAs) were above 90 %. Among eight antibiotics, sulfonamides (95.1 %) and fluoroquinolones (87.6 %) had the highest detection rates in couples. Approximately four-fifths of couples were simultaneously exposed to at least three different antibiotics, and more than half of them were exposed to low concentrations of antibiotics. 8.9 % and 9.2 % of wives and husbands had hazard index value of antibiotics exposure greater than 1. Antibiotic concentrations were associated with residence, sampling season, and diet frequency. In Anhui, nearly 98 % of childbearing couples have environmental exposure to antibiotics, and VAs and PVAs are the primary antibiotics. More than 8 % of couples had health risks due to antibiotic exposure. Several potential determinants of urinary antibiotics deserve more attention in future research.